PENGARUH MODIFIKASI PERMAINAN TRADISIONAL BOI TERHADAP KETERAMPILAN GERAK DASAR - Ribarto, Thoribius; Triansyah, Andika; Wati, Isti Dwi Puspita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this study was whether there is an effect of modification of traditional boi games. The purpose of this study was to improve students' basic motion skills through modification of traditional boi games in class III of SD Negeri 13 Tempunak. The method in this study used the experimental method in the form of pre-experimental designs with the form of the pretest-posttest. The population in this study were lower class students. The number of samples in this study were 15 students. Data analysis using t test analysis (influence test).Based on the results of the study, the results of tcount are 9.62 and t table is 2.132. This means that tcount> t table or 9.62> 2.132 then the hypothesis is accepted. This means that there are effects of modification of traditional boi games on basic motion skills in Grade III students of SD Negeri 13 Tempunak. The increase percentage is 21.66%.Keywords: Basic Motion, Mods, Traditional Games BoiAbstractThe problem in this study was whether there is an effect of modification of traditional boi games. The purpose of this study was to improve students' basic motion skills through modification of traditional boi games in class III of SD Negeri 13 Tempunak. The method in this study used the experimental method in the form of pre-experimental designs with the form of the pretest-posttest. The population in this study were lower class students. The number of samples in this study were 15 students. Data analysis using t test analysis (influence test).Based on the results of the study, the results of tcount are 9.62 and t table is 2.132. This means that tcount> t table or 9.62> 2.132 then the hypothesis is accepted. This means that there are effects of modification of traditional boi games on basic motion skills in Grade III students of SD Negeri 13 Tempunak. The increase percentage is 21.66%.Â Keywords: Basic Motion, Mods, Traditional Games Boi